Quicksand and passing - Larsen, Nella (New Jersey : Rutgers University Press, 1986)
Two novels of 1920s Harlem describe Helga Crane's search for freedom and personal expression, and Irene's friendship with Clare, who attempts to pass for white.
Includes bibliographical references.
Keywords: RACIALLY MIXED PEOPLE